Analysis Figure of Speech in Adele’s Songs - Nungki Lupita Prasetia; Masulah -; Waode Hamsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2014)
Language is an important means of communication to express our idea, emotion and feeling. Literature is creative and imaginative work of art spoken and written. Lyrics and poems, which are examples of literature, can express our feeling. Song is an imaginative awareness of experiences expressed through meaning, sound and rhythmic language choice so as to evoke an emotional response.There are many western musicians who use figure of speech in the songs. The researchers interested in Adele songs. Because her songs contain figure of speech and the researcher believes that these figure not yet well understood by the listeners. Her songs always contain about her experience.From this research, it is found in the songs that the kinds of figure of speech are personification, Metaphor and Synecdoche. The meaning in the figure of speech that is different from one song to another. Finally the researcher suggest the readers or other research want to conduct some researches that can analyze other types and aspect of figure of speech in the lyrics of songs composed or created by other singers.